HUBUNGAN PENEMPATAN PEGAWAI DENGAN KOMITMEN KERJA PEGAWAI PADA PT PELABUHAN INDONESIA II CABANG TELUK BAYUR PADANG - PRISTIA OKRIANI (Jurnal Bahana Manajemen Pendidikan, 2016)
This research describes the relationship between a work placement and the commitment of employee in PT Pelabuhan Indonesia II Teluk Bayur Padang branch. The population in this research were all employees of the PT Pelabuhan Indonesia II Teluk Bayur Padang branch, they were 103 employees. The number of samples were 47 people, taken by using proportional stratified random sampling technique. The instrument used in this research is a questionnaire in Likert scale model that had been tested for validity and realibility. Based on the research, a work placement of employees are in the right category of 85,33 % and the commitment of employee in the high category in the amount of 87,04%. There is a significant relationship between a work placement with the commitment of employee in PT Pelabuhan Indonesia II Teluk Bayur Padang branch with a correlation coefficient calculated = 0,41 > r table = 0,288 at the level of 95% and t = 3,05 > t tabel = 2,021 at the level of 95 %.